Computer algorithms : introduction to design and analysis - Baase, Sara; Gelder, Allen Van (Delhi : Pearson Education Asia, 2000)
Computer Science
Keywords: Computer algorithms; Sorting; Searching; Graphs; Dynamic programming; String matching; Parallel algorithms